2008
DOI: 10.1073/pnas.0806338105
|View full text |Cite
|
Sign up to set email alerts
|

Variable stoichiometry of the TatA component of the twin-arginine protein transport system observed by in vivo single-molecule imaging

Abstract: The twin-arginine translocation (Tat) system transports folded proteins across the bacterial cytoplasmic membrane and the thylakoid membrane of plant chloroplasts. The essential components of the Tat pathway are the membrane proteins TatA, TatB, and TatC. TatA is thought to form the protein translocating element of the Tat system. Current models for Tat transport make predictions about the oligomeric state of TatA and whether, and how, this state changes during the transport cycle. We determined the oligomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
243
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(282 citation statements)
references
References 41 publications
35
243
0
Order By: Relevance
“…Custom-written imaging software automatically separated and quantified these components and was capable of detecting spots with a total intensity of 2,000 counts or more. The full width at half maximum of spots was typically 300-350 nm, consistent with a FliM ring of diameter ∼50 nm convolved with the point spread function of a single YPet molecule in our microscope of width 250-300 nm (12,15,16). (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Custom-written imaging software automatically separated and quantified these components and was capable of detecting spots with a total intensity of 2,000 counts or more. The full width at half maximum of spots was typically 300-350 nm, consistent with a FliM ring of diameter ∼50 nm convolved with the point spread function of a single YPet molecule in our microscope of width 250-300 nm (12,15,16). (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…A home-built inverted TIRF microscope with 532 nm excitation wavelength was used, as described previously (12,15). Fluorescence emission was imaged at 50 nm∕pixel in frame-transfer mode at 25 Hz by a 128 × 128-pixel, cooled, back-thinned electron-multiplying charge-coupled device camera (iXon DV860-BI; Andor Technology).…”
Section: Methodsmentioning
confidence: 99%
“…outside the motor complex) was found to be 0.0088 + 0.0026 mm 2 s -1 . Furthermore, in another study, Leake et al [23] monitored the mobility of the inner membrane protein TatA in the twin-arginine translocation (Tat) system while complexed to the other Tat proteins. By labelling TatA with YFP they found that the diffusion coefficient, when corrected for the curvature of the membrane, decreased with increasing size of the Tat complex, ranging from about 0.1 mm 2 s -1 for complexes with about 10 TatA-YFP molecules to less than 0.01 mm 2 s -1 for complexes of near 100 TatA-YFP molecules.…”
Section: (B) Inner Bacterial Membranementioning
confidence: 99%
“…reorganization corresponds to TatA assembly rather than to TatA conformational change. To address this issue, we previously undertook direct imaging of YFP-labeled TatA (TatA-YFP) that had been expressed at native levels in living E. coli cells (31). Individual TatA complexes could be tracked by videorate fluorescence microscopy, and their oligomeric state could be estimated from their photobleaching traces.…”
Section: Significancementioning
confidence: 99%